KEMAMPUAN KOMUNIKASI ANTARPRIBADI MAHASISWA STIKOM MUHAMMADIYAH JAYAPURA ANTARA YANG MENGAKSES TWITTER DAN FACEBOOK (STUDI KOMPARASI) - Nurjayanti Nurjayanti (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
This research was conducted to analyze the differences in interpersonal communication skills among college students of STIKOM Muhammadiyah Jayapura between those who access Twitter and Facebook. The type of this research is quantitative research with a positivistic approach. This study uses an explanatory survey method and is a comparative study.The author uses Joseph A. Devito’s thoughts about the effectiveness of interpersonal communication. The population in this research were all college students of class 2017, 2018, and 2019 who accessed the Twitter and Facebook as many as 455 people.Determination of the number of samples used according to Arikunto, as much as 20% of total population, which is as many as 91 people, with a random sampling techniques. Methods of data collection using questionnaires and observations. The results showed that there were differences in the level of interpersonal communication among students college of STIKOM Muhammadiyah Jayapura between those who accessed Twitter and Facebook which were analyzed through parametric analysis (t test). This means that interpersonal communication in early adulthood is more effective using Facebook than Twitter. Keywords: Interpersonal Communication, Twitter, Facebook, Social Networkin